Selected Personnel Practices Relating to Research and Publication Among Management Faculty - Stark, Bobby J.; Miller, Thomas R. (Academy of Management Journal, 1976)
The article focuses on a study which identified personnel practices among management faculty in American Assembly of Collegiate Schools of Business schools which may influence faculty research and publication. A structured questionnaire was developed and mailed to school deans to collect data for the study. Results found that the normal teaching load could be adjusted for various reasons such as large class sizes and instruction of graduate courses. It also reveals that the university administration accepts research activity as a justification for a reduced teaching load.